2011
DOI: 10.1016/j.exer.2011.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Sustained elevation of extracellular ATP in aqueous humor from humans with primary chronic angle-closure glaucoma

Abstract: While the death of retinal ganglion cells in glaucoma is frequently associated with an elevation of intraocular pressure (IOP), the mechanisms connecting the two processes remain unclear. Extracellular ATP is released throughout the body in response to mechanical deformations. We have previously shown that patients with an acute rise in IOP have an elevated concentration of ATP in the anterior chamber. In the present study we ask whether ATP levels remain increased in patients with chronic elevations of IOP. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 49 publications
5
44
0
Order By: Relevance
“…To complicate the complexity of dinucleotides in the regulation of aqueous humour dynamics even more, studies have shown that glaucomatous patients present increased levels of Ap 4 A in their aqueous humour [7], which were almost 15 times higher in glaucoma patients than in healthy individuals. This increase in the dinucleotide levels has also been described in the case of ATP [15].…”
Section: Introductionsupporting
confidence: 69%
“…To complicate the complexity of dinucleotides in the regulation of aqueous humour dynamics even more, studies have shown that glaucomatous patients present increased levels of Ap 4 A in their aqueous humour [7], which were almost 15 times higher in glaucoma patients than in healthy individuals. This increase in the dinucleotide levels has also been described in the case of ATP [15].…”
Section: Introductionsupporting
confidence: 69%
“…We have previously demonstrated that humans with primary chronic angle closure glaucoma (PCACG) have a 14-fold increase in ATP levels in the anterior chamber. 26 While this finding supports the theory that a chronic elevation in IOP leads to a sustained elevation in extracellular ATP release, it was not possible to confirm this increase in the human retina as sampling was only justified from the anterior segment in these patients and not in the vitreal chamber. As the pathological changes to the retina and optic nerve head are most directly associated with vision loss, it is important to determine whether elevated extracellular levels of ATP also occur in the posterior eye during a chronic rise in IOP.…”
Section: Discussionmentioning
confidence: 72%
“…Pintor's group has extensively studied nucleotide-mediated IOP changes (18)(19)(20)39), and our data showing a hypotensive UDP effect was consistent with their results. In addition to the physiological roles of extracellular nucleotides, intraocular nucleotide levels have been reported to be elevated in the aqueous humor of glaucoma patients (13,14,40), indicating the pathological roles of dysregulated purinergic signaling in glaucoma. However, before this study, it was unclear whether the dysregulation of purinergic signaling contributed to the pathogenesis of glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleotides are released from various tissues and cells, including lens (6), trabecular meshwork (7), whole retina (8), corneal endothelial cells (9), retinal ganglion cells (RGCs) (10), retinal astrocytes (11), and ciliary body (CB) (12). ATP levels in the aqueous humor are highly elevated in glaucoma patients (13,14), and although IOP and ATP levels in the aqueous humor are positively correlated in patients (14), their interaction is undefined. Extracellular nucleotides including ATP bind to purinergic P2 receptors (15).…”
Section: Introductionmentioning
confidence: 99%